Assessing the active living environment in three rural towns with a high proportion of Native Hawaiians and other Pacific Islanders - Siosaia F Hafoka (Tabriz University of Medical Sciences, 2017)
Background: Existing literature on the built environment and physical activity in rural areas is very limited. Studies have shown that residents in rural areas are less likely to meet physical activity requirements than their counterparts living in urban and suburban areas. They are also less likely to have access to amenities and programs that promote physical activity. This study seeks to fill gaps in the literature by assessing the built environment in three rural towns in Hawaiʻi that have a high proportion of Native Hawaiians and other Pacific Islanders. Methods: The Rural Active Living Assessment (RALA) tools will be used to assess the built environment. The RALA has three components - Policy and Program Assessment (PPA), Town Wide Assessment (TWA), and Street Segment Assessment (SSA) which will be used to provide a comprehensive assessment of the active living environment. Assessments were completed in September and October 2016. Results: One assessment was completed in each town for the TWA and PPA. The SSA was completed with 60 segments (20 from each town). Conclusion: The RALA tools identified supports in these three rural towns. The assessment also identified barriers and gaps - especially with the town and school polices of each town.